The Course of Dyskeratosis Congenita Masked by Crohn’s Disease in a Primary School-Age Child: Case Report - Evgeniy E. Bessonov; Andrey N. Surkov; Anna L. Arakelyan; Stanislav D. Getmanov; Natalia V. Zhurkova; Leyla S. Namazova-Baranova (Педиатрическая фармакология)
Background. Dyskeratosis congenita (DC) is an extremely rare genetically determined syndrome associated with the formation of bone marrow depression and clinically manifested by abnormal pigmentation of the skin, onychodystrophy, cobble-stone tongue, damage to the gastrointestinal tract, lungs, etc. Pathology may occur under the guise of other, more common diseases, which leads to late verification of the diagnosis and affects the prognosis. Case report. The boy D., aged 7 years, was hospitalized with complaints of dysphagia, a change in the shape of nails, ulcerative lesions of the tongue, insufficient weight gain, thin stool. Laboratory: decrease in hemoglobin, pancytopenia, low concentration of IgG in blood serum. According to esophagogastroduodenoscopy— esophageal stenosis. Crohn’s disease was suspected, but the condition worsened against the background of anti-TNF therapy. According to the results of full-exome sequencing, a pathogenic variant c.1058C>T (chrX:154001427C>T; NM_001363.3; p.A353V) was detected in the DKC1 gene in a hemizygous state, on the basis of which DC was confirmed. Conclusion. Practitioners should be wary of DC, since its manifestations can often mimic other, more common pathological conditions, in particular inflammatory bowel diseases. The correct interpretation of the combination of clinical, laboratory and instrumental changes can help to get closer to the correct diagnosis even before receiving the results of a molecular genetic study and determine therapeutic tactics.